Minimum Effective Volume of Lidocaine for Ultrasound-Guided Costoclavicular Block. Issue 5 (1st September 2017) - Sotthisopha, Thitipan; Elgueta, Maria Francisca; Samerchua, Artid; Leurcharusmee, Prangmalee; Tiyaprasertkul, Worakamol; Gordon, Aida; Finlayson, Roderick J.; Tran, De Q.
Abstract : Background and Objectives: This dose-finding study aimed to determine the minimum effective volume in 90% of patients (MEV90) of lidocaine 1.5% with epinephrine 5 μg/mL for ultrasound-guided costoclavicular block. Methods: Using an in-plane technique and a lateral-to-medial direction, the block needle was positioned in the middle of the 3 cords of the brachial plexus in the costoclavicular space. The entire volume of lidocaine was deposited in this location. Dose assignment was carried out using a biased-coin-design up-and-down sequential method, where the total volume of local anesthetic administered to each patient depended on the response of the previous one. In case of failure, the next subject received a higher volume (defined as the previous volume with an increment of 2.5 mL). If the previous patient had a successful block, the next subject was randomized to a lower volume (defined as the previous volume with a decrement of 2.5 mL), with a probability of b = 0.11, or the same volume, with a probability of 1 − b = 0.89. Success was defined, at 30 minutes, as a minimal score of 14 of 16 points using a sensorimotor composite scale. Patients undergoing surgery of the elbow, forearm, wrist, or hand were prospectively enrolled until 45 successful blocks were obtained. This clinical trial was registered with ClinicalTrials.gov (ID NCT02932670 ). Results: Fifty-seven patients were included in the study. Using isotonic regression and bootstrap confidence interval, the MEV90 for ultrasound-guided costoclavicular block was estimated to be 34.0 mL (95% confidence interval, 33.4–34.4 mL). All patients with a minimal composite score of 14 points at 30 minutes achieved surgical anesthesia intraoperatively. Conclusions: For ultrasound-guided costoclavicular block, the MEV90 of lidocaine 1.5% with epinephrine 5 μg/mL is 34 mL. Further dose-finding studies are required for other concentrations of lidocaine, other local anesthetic agents, and multiple-injection techniques.